2020
DOI: 10.1002/ags3.12318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of D3 lymph node dissection with left colic artery (LCA) preservation compared to D3 without LCA preservation: Exploratory subgroup analysis of data from JCOG0404

Abstract: Aim We investigated the clinical impact of D3 lymph node dissection preserving left colic artery (LCA) compared to D3 without LCA preservation using data from JCOG0404. LCA preservation is expected to maintain adequate blood supply, which is effective in preventing anastomotic leakage, intestinal paralysis, and bowel obstruction. Whether D3 with LCA preservation (Group A) improves clinical outcomes following resection of sigmoid colon cancer compared to D3 without LCA preservation (Group B) is unclear. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
0
18
0
3
Order By: Relevance
“…Several previous studies have also shown that LCA preservation compared to non-preservation showed no significant differences with respect to the 5-year mortality in patients who underwent laparoscopic rectal cancer surgery, and this comparable success came with acceptable safety outcomes [ 10 , 12 , 13 ]. Data from the Japan Clinical Oncology Group Study showed that if the LCA was preserved, 5-year relapse-free survival (RFS) and OS were better than in the LCA non-preservation group (RFS: 83.7 and 80.5%, hazard ratio (HR) = 0.80, 95% CI: 0.51–1.26, OS: 96.3 and 91.1%, HR = 0.41, 95% CI: 0.19–0.89) [ 36 ]. Another Japanese study by Fujii [ 15 ] showed that the IMA ligation level was unrelated to anastomotic leakage and there was no significant difference in the long-term results between low and high ligation of the IMA.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have also shown that LCA preservation compared to non-preservation showed no significant differences with respect to the 5-year mortality in patients who underwent laparoscopic rectal cancer surgery, and this comparable success came with acceptable safety outcomes [ 10 , 12 , 13 ]. Data from the Japan Clinical Oncology Group Study showed that if the LCA was preserved, 5-year relapse-free survival (RFS) and OS were better than in the LCA non-preservation group (RFS: 83.7 and 80.5%, hazard ratio (HR) = 0.80, 95% CI: 0.51–1.26, OS: 96.3 and 91.1%, HR = 0.41, 95% CI: 0.19–0.89) [ 36 ]. Another Japanese study by Fujii [ 15 ] showed that the IMA ligation level was unrelated to anastomotic leakage and there was no significant difference in the long-term results between low and high ligation of the IMA.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages in D3 without LCA preservation have been identified in the prevention of the micrometastatic cell spillage through the en bloc lymph node dissection of the root of the inferior mesenteric artery (IMA); disadvantages include a higher possibility of anastomotic leakage and the sacrifice of the autonomic nerves around the IMA; no significant differences in terms of operation time and blood loss have been found. Despite a higher incidence of complications, D3 with LCA preservation was associated with a higher OS[ 33 - 37 ]…”
Section: Colorectal Cancermentioning
confidence: 99%
“…В літературі досі триває дискусія про місце лігування нижньої брижової артерії (НБА) при виконанні Д3 лімфодисекції з приводу лівобічного КРР. Загальноприйнятими є дві методики: лігування НБА в основі відходження від аорти та лігування НБА дистальніше відходження лівої ободової артерії (ЛОА) [3,4,6]. Лігування НБА в основі відходження від аорти дає можливість одним блоком провести Д3 лімфодисекцію та працювати в правильних анатомічних шарах [6].…”
unclassified
“…Лігування НБА в основі відходження від аорти дає можливість одним блоком провести Д3 лімфодисекцію та працювати в правильних анатомічних шарах [6]. Лігування НБА нижче відходження ЛОА дає можливість зберегти цю важливу судину для адекватного кровопоста-чання лівих відділів товстого кишечника та, відповідно, знизити ризик НША [3,4]. Проте слід також зважати, що дана опція є більш технічно складна та вимагає скелетизації НБА та її гілок іноді на досить широкому протязі [3].…”
unclassified
See 1 more Smart Citation